The Method of Interaction between the Ministry of Health and Medical EducationwithHealth-Related High Councils: A Model Design - Karimi, Amin; Mahfoozpour, Soad; Hesam, Somayeh; Damari, Behzad (The journal of contemporary issues in business and government, 2021)
Background and Aim: Formation of any kind of intersectoral cooperation and interaction requires a coherent and stable pattern and structure so that interaction is formed and continued in its light. There is little scientific evidence on features of an appropriate advocacy model in the area of interaction between the ministry of health and high councils of the country in line with the improvement of the public health, which shows the necessity of the present study. Materials and Methods: This was a qualitative research with a grounded theory approach, which analyzed the existing policies by defining a suitable advocacy model. Data was collected through in-depth semi-structured interviews, group discussion sessions, and document analysis. In total, 21 interviews and three group discussion sessions were held. It is notable that the participants were selected by purposive sampling with maximum diversity and snowball sampling to select the interviewees. Data analysis was performed in MAXQDA10 after the implementation of all interviews and group discussion meetings. Results: In this study, three detected main categories were “the role and share of the ministry of health in interaction with high councils”, “the role and share of high councils for health”, and “fair improvement of health indicators”. According to the results, four main roles of the ministry of health included evidence production, advocacy, determining expectations from councils, and managing changes. Regarding the share of the ministry of health in interacting with the councils, the highest score was related to the high council of education, whereas the lowest score was related to the high council of provinces. Regarding the main role and share of councils in the decrease of risk factors, the highest and lowest scores were allocated to the high council of health and food security and the high council of education, and the high council of space, respectively. Conclusion: According to the results of the study, the ministry of health,should act as a supporter and warn enough to increase the sensitivity of senior officials to the consequences of the current process and its effect on the prevalence of diseases. Therefore, it is recommended that the ministry of health re-defines and implements four roles of evidence production, advocacy, determining expectations, and managing changes within the framework of the developed model. On the other hand, high councils, which play an effective role in community health, should include a “health annex” in their decisions, approvals, and executive activities. Interaction of high councils with the ministry of health based on the basics of intersectoral cooperation will improve health indicators.